Theoretical research on reasonable shield support capacity in close-multiple coal seams with the coordinated mining: A case study of Qianjiaying coal mine. - Yang Li; Yuqi Ren; Xinghai Lei; Nan Wang; Xiangyang Jin; Guoshuai Li (PLoS ONE, 2022)
In order to assess the rationality of the rated shield support capacity (RSSC) experienced selection and guide the reasonable RSSC selection for the subsequent working faces of each coal seam, the coupling relationship between shield and roof strata was revealed during each coal seams mining. According to whether the fractured rock blocks generated by the main roof are articulated and whether the upper coal seam has been mined and influenced on the lower coal seam, two roof structure mechanical models of the rock blocks generated by the thick main roof and two calculation methods of a given load on the rock blocks are proposed. In addition, a selection method of roof structure model for maximum shield support capacity (MSSC) of close-multiple coal seams with the coordinated mining is put forward. Three roof structures to calculate the MSSC are established. Based on a case study of close-multiple coal seams with the coordinated mining in the Qianjiaying coal mine, the MSSC is calculated and analyzed in each coal seam combined with roof structure characteristics description, theoretical analysis, and field measurement. No.7, No.12-1, and No.5 coal seams mining are applicable to a voussoir beam balanced structure. No.8 coal seam mining is applicable to a balanced structure with a given load of loose body. No.9 coal seam mining is applicable to a voussoir beam balanced structure with a given load of loose body. Through the calculation, the MSSC of No.7, No.8, No.12-1, No.9, and No.5 coal seam is 3948.55kN, 4018.32kN, 4101.63kN, 3560.03kN, and 4015.30kN, respectively. And the RSSC suggested selection of each coal seam is 4500kN, 4300kN, 4300kN, 4000kN, and 4300kN, respectively. By field measurement, the RSSC experienced selection of each coal seam in the Qianjiaying coal mine is unreasonable with low support load utilization. However, after adopting the RSSC suggested selection in each coal seam, the support load utilization increased by 29.07%, 9.6%, 8.57%, 15.33%, and 11.39%.